Engineering research the perspective towards a sound conduct - David, Thevaneyan Krishta; Subramonian, Sivarao; Ramesh, S. (2023)
Research generally refers to a search for knowledge. It is a quest seeking the truth, moving from known to unknowns and discovers new or novel facts. Research is a common thing in our daily life. We do many kinds of research in our daily life to understand a certain fact or to help in decision makings. This write-up is the peel of research for a sound understanding of the basics of research especially in engineering studies. The objectives and motivations leading to research have been discussed together with types of research available. An appropriate research process, especially for engineering studies which are essentially important are also discussed here. The differences between research method and methodology also have been highlighted in this paper to ensure their respective significant attributes are well understood in conducting a research.